(untitled) (Journal of Environmental Science and Natural Resources, 2012)
The focus of this research was to analyze the yield, physico-chemical and nutritional quality of a cabinet dried tomato powder as affected by three (3) chemical treatments (KMS, CaCl2 and both). Dehydration process was carried out using a cabinet dryer at a constant air flow velocity of 0.7 m/s and air temperature in the range of 60-65oC based on preliminary tests by dipping in 0.2% (w/w) potassium metabisulphite (T1) and 1% (w/w) calcium chloride (T2) independently and 1% (w/w) calcium chloride (CaCl2) along with 0.2% (w/w) potassium metabisulphite (KMS) in water solution (T3) for 10 minutes. The effect of 3 pre-drying treatments on quality of cabinet dried tomato powder was analyzed by determining moisture content, rehydration ratio, total sugar, total acidity, fat, protein, ash, crude fiber, pH, total caroteniods, vitamin-C, minerals (calcium, iron, phosphorus) and sensory analysis. The results expressed that the treatment T3 achieved the highest yield of tomato powder (4.6 g/100 g). The control sample showed highest moisture content (6.9 g/100 g) and dipping in 1% CaCl2 along with 0.2% KMS presented the lowest moisture content (5.9 g/100 g). Sample T3 showed highest total sugar content (49.1 g/100 g). The study also depicted that the total carotenoids content in tomato powder was 0.21 mg/100 g which was lower than that of fresh tomato (2.1 mg/100 g). Micronutrients such as vitamin-C, Calcium, phosphorus and iron were found to be 35.30 mg/100 g, 336.72 mg/100 g, 105 mg/100g and 12.23 mg/100 g, respectively in case for T3 sample. Sensory analysis (color, texture, flavor and overall acceptability) of tomato powder was carried out by trained and untrained panelists and their interpretation was done by using statistical ANOVA Test. There was no significant difference between control and treated samples regarding to their texture, flavor and overall acceptability but significant difference was observed in case of color. DOI: http://dx.doi.org/10.3329/jesnr.v5i1.11590 J. Environ. Sci. & Natural Resources, 5(1): 253-265, 2012